Barriers to identifying occupational asthma among primary healthcare professionals: a qualitative study - Christopher M Barber; Gareth I Walters (BMJ Open Respiratory Research)
Introduction Occupational asthma (OA) accounts for one in six cases of adult-onset asthma and is associated with a large societal cost. Many cases of OA are missed or delayed, leading to ongoing exposure to the causative agent and avoidable lung function loss and poor employment-related outcomes. Enquiry about work-related symptoms and the nature of work by healthcare professionals (HCPs) is limited, evident in primary and secondary care. Potential reasons cited for this are time pressure, lack of expertise and poor access to specialists.Aim To understand organisational factors and beliefs and behaviours among primary HCPs that may present barriers to identifying OA.Methods We employed a qualitative phenomenological methodology and undertook 20–45 min interviews with primary HCPs in West Midlands, UK. We used purposive and snowball sampling to include general practitioners (GPs) and practice nurses with a range of experience, from urban and rural settings. Interviews were recorded digitally and transcribed professionally for analysis. Data were coded by hand, and thematic analysis was undertaken and determined theoretically until themes were saturated.Results Eleven HCPs participated (eight GPs, three nurses). Four themes were identified that were considered to impact on identification of OA: (1) training and experience, (2) perceptions and beliefs, (3) systems constraints, and (4) variation in individual practice. OA-specific education had been inadequate at every stage of training and practice, and clinical exposure to OA had been generally limited. OA-specific beliefs varied, as did clinical behaviour with working-age individuals with asthma. There was a focus on diagnosis and treatment rather than attributing causation. Identified issues regarding organisation of asthma care were time constraints, lack of continuity, referral pressure, use of guidelines and templates, and external targets.Conclusion Organisation and delivery of primary asthma care, negative OA-related beliefs, lack of formal education, and exposure to OA may all currently inhibit its identification.